Speciation processes in putative island endemic sister bat species: false impressions from mitochondrial DNA and microsatellite data. Issue 23 (20th November 2015) - Kuo, Hao‐Chih; Chen, Shiang‐Fan; Fang, Yin‐Ping; Cotton, James A.; Parker, Joe D.; Csorba, Gábor; Lim, Burton K.; Eger, Judith L.; Chen, Chia‐Hong; Chou, Cheng‐Han; Rossiter, Stephen J.
Abstract: Cases of geographically restricted co‐occurring sister taxa are rare and may point to potential divergence with gene flow. The two bat species Murina gracilis and Murina recondita are both endemic to Taiwan and are putative sister species. To test for nonallopatric divergence and gene flow in these taxa, we generated sequences using Sanger and next‐generation sequencing, and combined these with microsatellite data for coalescent‐based analyses. MtDNA phylogenies supported the reciprocally monophyletic sister relationship between M. gracilis and M. recondita ; however, clustering of microsatellite genotypes revealed several cases of species admixture suggesting possible introgression. Sequencing of microsatellite flanking regions revealed that admixture signatures stemmed from microsatellite allele homoplasy rather than recent introgressive hybridization, and also uncovered an unexpected sister relationship between M. recondita and the continental species Murina eleryi, to the exclusion of M. gracilis . To dissect the basis of these conflicts between ncDNA and mtDNA, we analysed sequences from 10 anonymous ncDNA loci with *beast and isolation‐with‐migration and found two distinct clades of M. eleryi, one of which was sister to M. recondita . We conclude that Taiwan was colonized by the ancestor of M. gracilis first, followed by the ancestor of M. recondita after a period of allopatric divergence. After colonization, the mitochondrial genome of M. recondita was replaced by that of the resident M. gracilis . This study illustrates how apparent signatures of sympatric divergence can arise from complex histories of allopatric divergence, colonization and hybridization, thus highlighting the need for rigorous analyses to distinguish between such scenarios.